Implementasi Work Life Balance dalam Meningkatkan Kinerja Pegawai pada Kantor Pelayanan Pajak Pratama Singosari - Oktoviona Wakman, Esther; Puspa Dewi, Mariana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to find out how the implementation of Work- Life Balance (WLB) affects employee performance at KPP Pratama Singosari. This study uses a qualitative approach with the type of case study research The data collection method is carried out using interviews and observations. Analysis The data is carried out through the stages of data reduction, data presentation, and conclusion drawn. The validity test of the data was carried out using the triangulation method. The results of interviews with four informants showed that the implementation of the WLB policy had a significant impact on employee productivity and welfare. However, challenges such as high workloads, frequently changing work schedules, and tight deadlines are still obstacles in maintaining this balance. Policies such as flexibility in working hours, overtime compensation, and open discussions between employers and employees have been proven to help reduce work pressure. This study concludes that the effective implementation of WLB's Work-Life Balance can improve employee performance, but needs to be strengthened by improved work schedule management, better communication, and welfare program support. The advice provided includes increasing work flexibility, schedule stability, and providing facilities that support the balance between work and personal life of employees. Keywords: Work-Life Balance, employee performance, schedule management, tax office, employee welfare.